(3x - y)(3x - 5y) and (2x + 1)(2x + 11)
4x2+3x+6+5x+3x+6 = 4x2+11x+12 when simplified
3x(2x + 1)
4X2+X3+3X+7Y+2X3 can only be simplified to 3X3+4X2+3X+7Y, because X3 and 2X3 are the only like terms.
-5y2+3x+2y
y=4x2+3x+8
x2-5-4x2+3x = 0 -3x2+3x-5 = 0 or as 3x2-3x+5 = 0
(3x - y)(3x - 5y) and (2x + 1)(2x + 11)
4x2+3x+6+5x+3x+6 = 4x2+11x+12 when simplified
x2-3x+2.25 is the same as 4x2-12x+9 and is (2x-3)(2x-3) when factored
4x2 - 3x - 9
3x(2x + 1)
3x-3x+4x^2+8x=4x^2+8x
4X2+X3+3X+7Y+2X3 can only be simplified to 3X3+4X2+3X+7Y, because X3 and 2X3 are the only like terms.
-5y2+3x+2y
(x3 + 4x2 - 3x - 12)/(x2 - 3) = x + 4(multiply x2 - 3 by x, and subtract the product from the dividend)1. x(x2 - 3) = x3 - 3x = x3 + 0x2 - 3x2. (x3 + 4x2 - 3x - 12) - (x3 + 0x2 - 3x) = x3 + 4x2 - 3x - 12 - x3 + 3x = 4x2 - 12(multiply x2 - 3 by 4, and subtract the product from 4x2 - 12)1. 4x(x - 3) = 4x2 - 12 = 4x2 - 122. (4x2 - 12) - (4x2 - 12) = 4x2 - 12 - 4x2 + 12 = 0(remainder)
The first equality is: x2 - 5 = -4x2 which gives 5x2 - 5 = 0 which is equivalent to x2 - 5 = 0 The second equality is: -4x2 = 3x which gives 4x2 + 3x = 0 The two results are inconsistent.